Bridging Local Culture and Scientific Literacy through the I-BATARA Learning Model: Validation and Implications for SDG 4 Quality Education - Wiwin Puspita Hadi; Erman Erman; Suyatno Sutoyo (Journal of Current Studies in SDGs, 2026)
Objective: To validate the I-BATARA learning model. The I-BATARA learning model, designed by integrating local cultural contexts, batik Tanjung Bumi, and scientific concepts, aims to improve science literacy. Method: Educational development research was used as the research design. Validation of the I-BATARA leaning model and instructional package involves two criteria: content validation and construct validation. Three experts in pedagogy, science content, and learning assessment validated the I-BATARA learning model and instructional package. Results: The research findings and data analysis indicated that the I-BATARA learning model has consistently yielded relevant outcomes. The I-BATARA model has met strict validity and reliability standards (with an agreement percentage >75%). Novelty: Validated learning support components include lesson plans, student textbooks, student worksheets, and scientific literacy tests. The I-BATARA learning model can be applied to foster students' scientific literacy through local cultural contexts. The model is suitable for meaningful science learning and for developing students' social skills, while offering practical implications for SDG 4 (Quality Education) by promoting culturally relevant, context-based scientific literacy instruction.